OBJECT THEFT DETECTION SYSTEM - Mohd Suffian, Nurulain (Universiti Teknologi PETRONAS, 2009)
Often, in our daily life, we sometimes do not notice our belongings which we put it on the table or on the walls .are taken or stolen by somebody. Jn a picture gallery for example, video surveillance are very essential to monitor the arts and pictures which are exposed for viewing to the public. However, human operators often lose his focuses if he needs to monitor the videos, which may probably range from one to more than one, in a long hour. Therefore, when a ste_eling scenes occ.urs,they may not be alerted in an instance. Thus, a semiautomatic tools or system to alert the human operator when this type of event occurs may become a helpful method to assistthe human operators in performing their job efficiently and effectively. By using object recognition techniques together with video image processing tools available in MATL;\B®, this paper discussed the implementation of the available methods to come oljr with Ill'\ Object T!u;ft Detection System which can detect stolen object in real-time environment. and issue an alarm when emergency occurs, lil